Fast and Selective Against Bacteria. Issue 4 (December 2013) - Neugebauer, Ute; Kloß, Sandra; Schröder, Ulrich‐Christian; Rösch, Petra; Popp, Jürgen
Abstract Raman microscopy combined with chemometrics is employed to identify bacteria causing urinary tract infections from urine samples. With this method, a reliable result is obtained within three hours. This is much faster than the current gold standard urine culture as the spectroscopic approach requires no cultivation steps and a few single bacteria are sufficient. In addition, Raman spectroscopy can be employed to determine the antibiotic susceptibility of the bacteria. Thereby it is possible to not only quickly identify the pathogens but also to select the appropriate antibiotics for the patient avoiding inefficient treatment due to resistances. With this complex spectral information, tailored antibiotic therapy is possible already at a much earlier hour.